Towards cellular imaging with chemical and molecular specificity: Raman and coherent anti-Stokes Raman (CARS) microscopy - Noestheden, Matthew (University of Ottawa (Canada), 2006)
The lack of photobleaching, minimal sample heating, and high acquisition rates associated with coherent anti-Stokes Raman scattering (CARS) microscopy make it an attractive approach for the chemically specific in vivo imaging of dynamical processes. However, imaging capabilities are currently confined to classes of macromolecules as opposed to specific molecular targets. The use of cyano and deuterium functional group labels, which possess Raman modes in a spectral region devoid of endogenous cellular resonances, has the potential to surmount this limitation, enabling imaging with chemical and molecular specificity using CARS microscopy. Herein, cyano and deuterium vibrational modes have been incorporated into Raman and CARS contrast agents capable of mediating biomolecular modification. Application of this approach will be demonstrated using hepatitis C virus (HCV) RNA and two model protein systems with the end goal of investigating dynamical aspects of HCV molecular virology in real-time in vivo using CARS microscopy. The addition of exogenous CARS labels to a biomolecule can have serious structural and functional consequences that may lead to the expression of a phenotype dictated by the effects of the modification rather than the system under investigation. Therefore, the structural and functional consequences of introducing CARS labels needed to be investigated before applying cyano and deuterium modified HCV RNA and proteins to in vivo analysis using CARS microscopy.
Keywords: Chemistry, Analytical.